2020
DOI: 10.3847/1538-4357/ab6bce
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Dynamics of Convective Turbulence in the Solar Granulation by Spectral Line Broadening and Asymmetry

Abstract: In the quiet regions on the solar surface, turbulent convective motions of granulation play an important role in creating small-scale magnetic structures, as well as in energy injection into the upper atmosphere. The turbulent nature of granulation can be studied using spectral line profiles, especially line broadening, which contains information on the flow field smaller than the spatial resolution of an instrument. Moreover, the Doppler velocity gradient along a line-of-sight (LOS) causes line broadening as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…• Full width at half maximum (FW HM) fluctuations, hereafter referred to as δF, which convey information about changes of the non-thermal motions in the observed region, contributing to the broadening of the spectral line profiles, as for turbulent motions (e.g., [14]); • Bisector variations of the line profiles associated with the vertical velocity gradients in the observed region; these variations are evaluated using the definition of the line asymmetry parameter A reported in Hanslmeier et al [74], and are hereafter referred to as δA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Full width at half maximum (FW HM) fluctuations, hereafter referred to as δF, which convey information about changes of the non-thermal motions in the observed region, contributing to the broadening of the spectral line profiles, as for turbulent motions (e.g., [14]); • Bisector variations of the line profiles associated with the vertical velocity gradients in the observed region; these variations are evaluated using the definition of the line asymmetry parameter A reported in Hanslmeier et al [74], and are hereafter referred to as δA.…”
Section: Discussionmentioning
confidence: 99%
“…The imaging observations of the photosphere obtained with these methods have provided information about the morphology and evolution of the granulation pattern [7,8], its dynamics including vortex flows [9] and advection by larger scale flows [10]. Moreover, the analysis of spectral lines measurements, which reveals the properties of the convective plasma logged in the line shape, has shown the height-dependence of the velocity structure of flows in granules and intergranular lanes [11,12] and the narrow transition zones where granular flows bend down [13], as well as the presence of the small-scale turbulent motions therein [14]. Some studies have also reported convective patterns at scales larger than those of the granulation, in particular of the mesogranulation (with a spatial scale of 5-10 Mm, e.g., [15][16][17][18][19]), supergranulation (with a spatial scale of 20-50 Mm, [20][21][22]) and giant cells (with a spatial scale of 100 Mm and larger, [23][24][25]).…”
Section: Introductionmentioning
confidence: 99%
“…Following the approach of Hanslmeier and Nesis [ 60 ], we computed maps of four physical quantities (hereafter also referred to as parameters) from our observations. These maps show: Continuum intensity fluctuations, hereafter referred to as , which are associated with the temperature differences between hotter granules and cooler intergranular lanes in the observed region; Line-of-sight (LoS) velocity fluctuations, hereafter referred to as , which are related to velocity differences between the upward and downward plasma motions in the studied region, and are encoded in the Doppler shift of the observed spectral lines; Full width at half maximum ( ) fluctuations, hereafter referred to as , which convey information about changes of the non-thermal motions in the observed region, contributing to the broadening of the spectral line profiles, as for turbulent motions (e.g., [ 14 ]); Bisector variations of the line profiles associated with the vertical velocity gradients in the observed region; these variations are evaluated using the definition of the line asymmetry parameter A reported in Hanslmeier et al [ 74 ], and are hereafter referred to as . …”
Section: Observations and Data Analysismentioning
confidence: 99%
“…Full width at half maximum ( ) fluctuations, hereafter referred to as , which convey information about changes of the non-thermal motions in the observed region, contributing to the broadening of the spectral line profiles, as for turbulent motions (e.g., [ 14 ]);…”
Section: Observations and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation